2015
DOI: 10.1681/asn.2014020192
|View full text |Cite
|
Sign up to set email alerts
|

EGF Receptor Deletion in Podocytes Attenuates Diabetic Nephropathy

Abstract: The generation of reactive oxygen species (ROS), particularly superoxide, by damaged or dysfunctional mitochondria has been postulated to be an initiating event in the development of diabetes complications. The glomerulus is a primary site of diabetic injury, and podocyte injury is a classic hallmark of diabetic glomerular lesions. In streptozotocin-induced type 1 diabetes, podocyte-specific EGF receptor (EGFR) knockout mice (EGFR podKO ) and their wild-type (WT) littermates had similar levels of hyperglycemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
115
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 46 publications
(58 reference statements)
4
115
1
Order By: Relevance
“…3, D-F). We also observed glomerular up-regulation of the EGFR heterodimerization partner of ErbB4 in these samples, confirming similar findings by others (47)(48)(49)(50). Co-staining with podocyte marker synaptopodin showed that the increase in their expression co-localized within podocytes in the glomeruli.…”
Section: Mir-146 In Podocytes and Diabetic Injurysupporting
confidence: 92%
See 2 more Smart Citations
“…3, D-F). We also observed glomerular up-regulation of the EGFR heterodimerization partner of ErbB4 in these samples, confirming similar findings by others (47)(48)(49)(50). Co-staining with podocyte marker synaptopodin showed that the increase in their expression co-localized within podocytes in the glomeruli.…”
Section: Mir-146 In Podocytes and Diabetic Injurysupporting
confidence: 92%
“…The results presented here suggest that both proteins are induced in the diabetic glomeruli. Similarly, the pan-ErbB kinase inhibitor erlotinib binds to EGFR with a significantly higher affinity (2 nM) than ErbB4 (55) and has been shown to protect against DN (47)(48)(49)(50), which might suggest that the efficacy of erlotinib observed here is likely due to its inhibition of EGFR over ErbB4, suggesting that EGFR is the main culprit in disease pathogenesis. However, here we find that, at least with the TGF-␤1 treatment of podocytes in vitro, ErbB4 levels increased in cells without affecting levels of EGFR, suggesting that ErbB4 up-regulation has pathogenic relevance.…”
Section: Mir-146 In Podocytes and Diabetic Injurymentioning
confidence: 78%
See 1 more Smart Citation
“…The increased production of ROS plays a key role in the development and progression of DN [23] . Oxidative stress occurs when ROS affect the balance between oxidative pressure and antioxidant defense.…”
Section: Discussionmentioning
confidence: 99%
“…10 Studies by us and others have found that prolonged EGFR activation in diabetic animals mediated aberrant activation of a TGF-b1-smad signaling pathway, and inhibition of EGFR signaling in diabetic kidney by pharmacologic or genetic strategies markedly preserved renal function and slowed DN progression. [11][12][13][14] The elucidation of the role of the Hippo pathway, which is conserved from Drosophila to mammals, has provided new insights in understanding the regulation of cell proliferation, cell death, and cell differentiation to control organ size. The core components of the Hippo signaling pathway-Warts, Salvador, Hippo, and Mats-were discovered in genetic screens in Drosophila for tumor suppressor genes.…”
mentioning
confidence: 99%